Cationic Mismatch Effect Induced by Double Substitution on the Structural and Magnetic Properties of La0.5Ca0.5MnO3 - Wadie Abdelhedi; Akram Krichene; Wahiba Boujelben; Nassira Chniba-Boudjada (Magnetochemistry)
In this study, we aimed to induce controlled structural disorder through a double substitution approach in the La0.5Ca0.5MnO3 compound by investigating La0.5−xRexCa0.5−yAeyMnO3 compounds with x = 0.05 and 0.1 and Re = Eu, Nd, Gd, Pr, and Ae = Ba and Sr. The y values are adjusted to maintain a constant average ionic radius (<rA> = 1.198 Å) and an unchanged Mn3+/Mn4+ ratio. These samples were synthesized using the sol–gel method. XRD analysis confirms structural stability despite the induced disorder, showing subtle lattice distortions. Magnetic measurements reveal that introducing low disorder annihilates the charge ordered (CO) state, enhances double-exchange interactions, and influences the ferromagnetic (FM) volume fractions. Moderate disorder strengthens AFM–CO state, triggering a first–order metamagnetic transition and reducing the Curie temperature value. Magnetic field-dependent magnetization data show disorder dependent magnetic behavior and suggest the presence of the Griffiths phase for all samples, confirming the role of structural disorder in tuning magnetic phase coexistence. Pr-based samples display a considerable magnetocaloric effect near their Curie temperature.